Anterior cruciate ligament rupture, reconstruction, rehabilitation and recovery: The personal experiences of competitive athletes. - Borman, Anel (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScSportSc)--Stellenbosch University, 2018.